(untitled) (Journal of Rangpur Medical College, 2026)
Background: Despite great improvement in the management of lupus nephritis, it remains the most frequent cause of SLE-related mortality. It has diversities of clinical and histological presentations. Objective: The aim of this study was to observe the most common clinicopathological presentations of lupus nephritis (LN). Methods: This cross-sectional observational study was conducted among thirty patients with lupus nephritis, admitted into department of Medicine, Rangpur Medical College and Hospital during June, 2023 to May, 2024 through convenient sampling. After written consent, all patients were undergone renal biopsy and tissue was analyzed for histopathological examination. After compilation data was analyzed by SPSS version 25.0. Results: Out of thirty patients female were 27(90%) and male 3(10%), most of them 21(70.00%) were at childbearing age between 18 and 35 years, the mean age was 24.16±4.23 years. The most frequent clinical features were edema (100%), joint pain/arthralgia 18(60.00%), fever 16(53.33%) and oral ulceration 11(36.66%). On examination 21(70%) patients were anaemic, 18(60%) patients had microscopic hematuria and proteinuria >0.5 gm/24 hours was noticed in all patients. Among the respondents 18(60.00%) patients had nephrotic range of proteinuria. 10(33.33%) patients had serum creatinine >1.40 mg/dl. On serological test 28(93.3%) patients had a positive ANA, 27(90%) patients had a positive anti-ds DNA. The most common histological feature was class IV in 17(56.70%) patients, followed by 6(20.00%) patients had Class II, 4(13%) patients had Class V and 2(6.7%) patients had Class III lupus nephritis. Conclusion: Generalized swelling/ edema was the commonest clinical presentation with class IV lupus nephritis on histology . J Rang Med Col.2026 Mar;11(1): 202-207